FAKTOR GAYA HIDUP KELUARGA BERISIKO DIABETES MELITUS DI DESA BELIMBING, KECAMATAN REJOTANGAN, KABUPATEN TULUNGAGUNG (Family Lifestyle Factors as The Risk of Diabetes Mellitus in Blimbing, Rejotangan, Tulungagung) - Aesthetica Islamy; Berlian Yuli Saputri; Suharyoto Suharyoto; Ketjuk Herminaju; Suciati Suciati; Niatasya Septa Ericha Putri (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Non-Communicable Diseases (NCD) is the leading cause of death worldwide. Diabetes Mellitus (DM) is one of four non-communicable diseases that can be caused by lifestyle factors. There are 4 family lifestyles that are a risk of causing diabetes mellitus, namely physical activity (exercise habits), diet (habits to consume sugary drinks), smoking habits, and the frequency of monitoring blood sugar levels. This study aims to describe the lifestyle of families at risk of diabetes mellitus in Blimbing Village, Rejotangan District in 2022. The research design used is descriptive quantitative. The population and sample of this study were families who lived in the same house with people has diabetes mellitus as many as 20 samples, provided that they met the inclusion and exclusion criteria. The variable used in this study is a single variable, namely the lifestyle of the family at risk of diabetes mellitus. Furthermore, data collection was carried out using a questionnaire, after which the data was processed by editing, coding, data entry, tabulation, and analyzed by percentage. The results of the research from 20 total respondents can be seen that most of the respondents have a bad lifestyle as many as 13 people (65%), respondents have very bad lifestyle as many as 4 people (20%), and respondents with a good lifestyle as many as 2 people (10%). The conclusion from the results of the study shows that special attention is needed to control the risk of diabetes mellitus seen from the aspect of family lifestyle, most of which have a bad lifestyle in order to start a good lifestyle.